Pengaruh Pembelajaran Dalam Jaringan Dengan Aplikasi Google Classroom Terhadap Minat Belajar Siswa Di Smp Plus Muda Prakarya - edy; M. Farhan Wahid; Zaenal Abidin (STIT Sirojul Falah Bogor, 2022)
The method used is a quantitative method. This method is used to determine whether there is an effect of online learning with the Google Classroom application on students' interest in learning at SMP Plus Muda Prakarya. The research instrument used to obtain data is by using product moment correlation analysis. The variable studied in this study is the effect of Online Learning (X) on Students' Interest in Learning (Y). Based on the product moment analysis, the value of